2007
DOI: 10.1016/j.jtcvs.2006.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental and neuroradiologic outcomes in patients with univentricular heart aged 5 to 7 years: Related risk factor analysis

Abstract: In children with univentricular heart, intellectual and neurologic deficits are common. Perioperative and postoperative risk factors related to the primary phase and bidirectional Glenn operation contribute to these deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 25 publications
6
71
1
Order By: Relevance
“…[23][24][25][26] In this study, 25% of the patients showed significant cognitive delays. Only 1 patient had a diagnosis of mild mental retardation, indicating that HTx children scoring in the mentally retarded range often did not have the appropriate diagnoses.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[23][24][25][26] In this study, 25% of the patients showed significant cognitive delays. Only 1 patient had a diagnosis of mild mental retardation, indicating that HTx children scoring in the mentally retarded range often did not have the appropriate diagnoses.…”
Section: Discussionmentioning
confidence: 47%
“…7 Immunosuppressive medication may cause tremor, 27 which may account for part of this impairment, but children with surgically corrected heart diseases and children on the waiting list for heart or heart-lung transplant do show fine motor and visuospatial difficulties. 26,28,29 Arithmetic difficulties associated with visuospatial deficits have occurred in the HTx population. 3,4,11 Parents of HTx children in this study reported poor learning in mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Children with transposition of the great arteries (TGA) or hypoplastic left heart syndrome (HLHS) have received the most attention in the literature 5 6. Historically, HLHS has carried the greatest risk of mortality and morbidity but, as survival has improved, significant impairment has emerged in survivors 5 7 8. Despite a perception that the cognitive function of infants with TGA is relatively spared compared with other lesions, assessments of survivors even 16 years after surgery have revealed significant, although subtle impairment in their neurodevelopment and intellectual performance 9.…”
Section: Introductionmentioning
confidence: 99%
“…For children with univentricular heart (UVH), surgical palliation is available [1][2][3][4]. The aim of the treatment protocol is what is called Fontan circulation.…”
Section: Introductionmentioning
confidence: 99%